Traditional Chinese Medicine Fuzheng Huayu Prevents Development of Liver Fibrosis in Mice - Jiang, Chunyan; Iwaisako, Keiko; Cong, Min; Diggle, Karin; Hassanein, Tarek; Brenner, David A; Kisseleva, Tatiana (Archives of Clinical and Biomedical Research, 2020)
Aim: To investigate the therapeutic effect of FZHY on hepatic fibrosis in mice and to determine the mechanism of its action. Methods: Wild type mice were subjected to toxic (carbon tetrachloride, CCl4) or cholestatic (bile duct ligation, BDL). Upon induction of liver fibrosis, mice were treated with FZHY (4.0g/kg, 2w, oral gavage) or vehicle (PBS). Livers were analyzed by Sirius Red staining, immunostaining and RT-PCR for pro-fibrogenic and pro-inflammatory genes. The effect of FZHY on hepatocytes, inflammatory responses, activation of fibrogenic myofibroblasts, and ROS production was assessed. Results: FZHY strongly inhibited the development of CCl4- and BDL-induced liver fibrosis in mice. Liver fibrosis was significantly improved in FZHY-treated mice, as demonstrated by reduced content of hepatic hydroxyproline and Sirius Red positive area. Moreover, the number of SMA +and Desmin+ myofibroblasts was significantly reduced in the livers of FZHY-treated mice, and correlated with downregulation of the mRNA levels of α-SMA, collagen-α1(I), tissue inhibitor of matrix metalloproteinase-1 (TIMP-1), TGF-β1 and its receptor TGF-βRI, and platelet-derived growth factor-β (PDGF-β), suggesting that FZHY inhibits activation of fibrogenic myofibroblasts. Furthermore, administration of FZHY markedly decreased recruitment of F4/80+ inflammatory macrophages to the livers of CCl4- and BDL-injured mice, and this effect was associated with downregulation of monocyte chemoattractant protein-1(MCP-1) and macrophage inflammatory protein-1 (MIP-1) mRNA. In addition, the lipid peroxidation products 4-hydroxynonenal (4-HNE) and malondialdehyde (MDA) were reduced, demonstrating that treatment with FZHY can effectively block ROS production in livers of CCl4- and BDL-injured mic